2019
DOI: 10.1038/s41598-019-46570-5
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on latent TB infection screening and its association with TB incidence in HIV patients

Abstract: Latent TB infection (LTBI) in HIV patients, its treatment, and immunological recovery following highly active antiretroviral therapy (HAART) could interact and impact TB disease progression. We aim to examine the factors associated with LTBI and TB disease development among HIV patients. Longitudinal clinical and laboratory data were accessed from the largest HIV specialist clinic in Hong Kong, where HAART and yearly LTBI screening are routinely provided for HIV patients. Between 2002 and mid-2017, among 2079 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Median CD4/CD8 ratio at time of ART initiation in patients who developed incident TB in our cohort was similar to recent reports [18,44]. However, no significant difference in the average change of ratio over time on ART was seen in patients developing TB compared to patients remaining free of TB [44].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Median CD4/CD8 ratio at time of ART initiation in patients who developed incident TB in our cohort was similar to recent reports [18,44]. However, no significant difference in the average change of ratio over time on ART was seen in patients developing TB compared to patients remaining free of TB [44].…”
Section: Discussionsupporting
confidence: 89%
“…Cumulative findings have demonstrated that antiretroviral therapy (ART) reduces the risk of developing tuberculosis (TB) significantly [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Despite the advent of ART, however, TB remains the major cause of death and morbidity among patients co-infected with HIV-1 in sub-Saharan Africa (SSA) [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-two cohorts reported the type of clinic where PLHIV were evaluated for TPT, and 40 (64%) of these cohorts were seen in HIV clinics. Twenty-one cohorts [ 17 , 66 79 ] did not use LTBI tests, while 49 cohorts [ 17 55 ] used LTBI tests; 22 used only TST, 12 used only IGRA, and 15 used either IGRA or TST. Among the 56 (80%) studies that reported the type of TPT regimen, mono-isoniazid regimens were the primary regimen prescribed in 50 cohorts (89%), and only one (2%) of the included cohorts primarily prescribed rifamycin-based short regimens (3 to 4 months of rifampicin and isoniazid) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…From our statistical analyses on the same data set, CD4 lymphocyte level, ART status, right of abode, and LTBI testing and treatment were important risk factors for TB development. 21 As the study population was relatively young, age by itself was not a significant risk factor for TB incidence. Tuberculosis reactivation rates by right of abode, ART status, CD4 lymphocyte level, and history of LTBI treatment were determined for model parameterization (eTable 3 in the Supplement).…”
Section: Methodsmentioning
confidence: 87%
“…In Hong Kong, nonlocal infections (inferred from infections in non-Chinese individuals and residents without right of abode) were also not significantly associated with positive subsequent LTBI tests. 21 To identify patients who had false-negative test results in previous LTBI tests, targeted subsequent LTBI tests by risk factor (strategy B), which cost less than annual testing strategy, might be an option. The risk-based testing strategy is currently recommended by the National Institute for Health and Care Excellence and the British HIV Association in the United Kingdom; this strategy involves testing HIV-positive individuals based on specific criteria, such as CD4 lymphocyte levels, country of origin, and ART duration.…”
Section: Discussionmentioning
confidence: 99%